Baha, Bakwet: Implikasyon ng Kalamidad sa Kakayahan ng mga Kababaihang Naninirahan sa Evacuation Center ng Brgy. San Vicente, Angono - Obedicen, Victor G. (Review of Women's Studies; Vol 23 No 1-2 (2013): Review of Women's Studies Volume XXIII, Numbers 1-2 (January-December 2013), 2023)
This paper explores how disaster situations exacerbate women's conditions and further reinforce their marginalization. It also tries to relate how institutional arrangements shape Disaster Risk Reduction and Management programs and activities that tend to neglect or subordinate women's needs to strengthen their capacities and lessen their vulnerabilities; and the long-term implications in developing their human capabilities towards their well-being. The study was done by culling out experiences of mothers living in a covered basketball court-turned evacuation center in Angono, Rizal. This paper recommends taking advantage of recent developments at the global and national levels that provided opportunities to advance recognition and address women's rights in disaster situations. It also makes a case for the importance of organizing communities around women's issues and aspirations in transforming institutions.